Engineering Human Beige Adipose Tissue - Gonzalez Porras, Maria A.; Stojkova, Katerina; Acosta, Francisca M.; Rathbone, Christopher R.; Brey, Eric M. (Frontiers in Bioengineering and Biotechnology, 2022)
In this study we describe a method for generating functional, beige (thermogenic) adipose microtissues from human microvascular fragments (MVFs). The MVFs were isolated from adipose tissue acquired from adults over 50 years of age. The tissues express thermogenic gene markers and reproduce functions essential for the potential therapeutic impact of beige adipose tissues such as enhanced lipid metabolism and increased mitochondrial respiration. MVFs serves as a potential single, autologous source of cells that can be isolated from adult patients, induced to recreate functional aspects of beige adipose tissue, and enable rapid vascularization post transplantation. This approach has the potential to be used as an autologous therapy for metabolic diseases or as a model for the development of a personalized approach of high-throughput drug development/screening for adipose tissue.